Tailoring epoxy resin impact performance by varying coconut coir fiber reinforcement - Muhammad Budi Haryono; Hisyam Ma'mun; Aan Burhanuddin; Muhammad Faesal Febriandyono; Joko Yulianto (Fakultas Teknik, Universitas Lampung, 2026)
Epoxy resin generally exhibits low impact toughness and tend to be brittle when subjected to high load impacts. Indonesia in an archipelagic country that has abundant coconut plants. The purpose of this study is to utilize coconut coir fiber waste as an alternative to improve the impact toughness of epoxy resin. Therefore, this research uses coconut coir fiber as a reinforcement in epoxy resin matrix composites, varying the volume fraction of coconut coir fibers from 0% to 50%. The results show that increasing the volume fraction of coconut coir fiber from 0% to 50% decreases the mass of the epoxy resin but increases its impact toughness. The epoxy resin mass decreases from 11.0±0 grams to 9.3±0.6 grams, while the impact toughness increases from 0.027±0.01 J/mm2 to 0.075±0.02 J/mm2.